2016
DOI: 10.1039/c6nj01957a
|View full text |Cite
|
Sign up to set email alerts
|

Selective chromo-fluorogenic detection of trivalent cations in aqueous environments using a dehydration reaction

Abstract: Trivalent cations induced a dehydration reaction of a chemodosimeter in water that is coupled with colour and emission changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Sensor 87 suffered from the selectivity issue but the detection limit was excellent with a LOD value of 7.2 ppb for As 3+ ion. A chromogenic-fluorescence probe 88 [150] was applied for detection of As 3+ along with Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ ions. In a Water-MeCN (95:5, v/v) solution, in presence of As 3+, the color of 88 changed to violet from colorless along with quenching of fluorescence.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Sensor 87 suffered from the selectivity issue but the detection limit was excellent with a LOD value of 7.2 ppb for As 3+ ion. A chromogenic-fluorescence probe 88 [150] was applied for detection of As 3+ along with Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ ions. In a Water-MeCN (95:5, v/v) solution, in presence of As 3+, the color of 88 changed to violet from colorless along with quenching of fluorescence.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…When Cd 2+ , Al 3+ , Cu 2+ , etc., were added to the chemosensor TP in EtOH, there was no significant fluorescent response, except for In 3+ , which showed a fluorescence emission at 460 nm [22] due to the CHEF effect. The distinctive selectivity of probe 3 towards In 3+ is assigned to the size effect and the hard-soft principle, indicating that it could effectively distinguish In 3+ from Al 3+ and Ga 3+ because of their alike properties [23] (Scheme 3). UV-Vis titration showed that the absorption band (exhibited by the free sensor) gradually decreased at 310 nm and a new band at 379 nm emerged due to the presence of In 3+ .…”
Section: Indiummentioning
confidence: 99%
“…This is achieved by generating a change in the electronic, conformational, or optical properties of a supramolecular structure, resulting in a chemical response translated into a signal. Colorimetric and fluorometric sensors use changes in optical properties, absorption or emission, as an output signal [1][2][3][4][5][6]. The great development that spectroscopic methods have undergone in the 20th century made it possible to have adequate analytical techniques for the translation of the signal produced in the coordination process and its subsequent interpretation.…”
Section: Introductionmentioning
confidence: 99%